6x+12x+5y-6y=

Simple and best practice solution for 6x+12x+5y-6y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+12x+5y-6y= equation:


Simplifying
6x + 12x + 5y + -6y = 0

Combine like terms: 6x + 12x = 18x
18x + 5y + -6y = 0

Combine like terms: 5y + -6y = -1y
18x + -1y = 0

Solving
18x + -1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.
18x + -1y + y = 0 + y

Combine like terms: -1y + y = 0
18x + 0 = 0 + y
18x = 0 + y
Remove the zero:
18x = y

Divide each side by '18'.
x = 0.05555555556y

Simplifying
x = 0.05555555556y

See similar equations:

| 12x*18y=4800 | | 5x^2-4xy-2x+y^2+2= | | (3w+4w)squared= | | -5x+77=4x-103 | | x^2+6x-22=-6 | | 5x^2+y^2-4xy-2x+5=0 | | a+10=7a | | 8x^2-34x=-30 | | (4n-1)=-6 | | 3w+4wsquared= | | zw+7x=c | | 5z+7z=17 | | 5y+6x=5 | | Y=5.0+.30X | | 7x+4=7(x+1) | | f(x)=x^3+5x^2+2x-8 | | 3b=8b-11 | | x^2+27x-198=0 | | 3(-x-2)=3x+6 | | -3v+5v=-16 | | 15y=45y-30 | | 5x+23=-x+5 | | 6(t-5)+6t=4(3t+4)-12 | | 9x+51y=26 | | 3xy=1+x | | 9c-2c= | | 7(6+4k)=-18+8k | | 2w-16+y=180 | | -29+X=-3 | | 15=-9+4w+2w | | 7y=42y+60 | | 21x=176 |

Equations solver categories